Wear Resistance Research and Its 2-factor Modeling of Nanoscaled Silicon Carbide Detonation Coatings - Dovgal, A.H.; Pryimak, L.B.; Varijukhno, V.V. (Problems of Tribology, 2023)
This research is related to the spheres of wearproof coating testing. The SiC coating has been deposited on the medium carbon steel using detonation deposition using the magnet coil flux of back direction. It has been established that only nanoscaled particles are deposited on the surface which had been accumulated in aggregates of different shape. The structure of the obtained coating has been thoroughly researched on the electronic microscope in previous publication. The obtained coating has been developed for testing on the friction bench modeling the friction process that is taking place in the couple of main and rod journals of internal combustion engines. The coating has also the corrosion protection properties. The nanoscaled coating on mild carbon steel had been tested under specified conditions and their friction surfaces had been researched on electronic microscope with the view of determination of wear mechanism. The two-factor modeling of the wear rate and friction factor has been done and three-dimensional diagrams have been plotted and analyzed.